A cross-sectional analytical survey on ACL depressive syndrome at a tertiary care hospital - Rastogi, Aavrati; Kalia, Roop B.; Meena, Pradeep K. (International Journal of Research in Medical Sciences, 2025)
Background: One of the most prevalent and incapacitating injuries affecting active people is an anterior cruciate ligament (ACL) injury. There is evidence of the physical effects of ACL injuries, but there is now growing evidence of the psychological toll, which is referred to as ACL depressive syndrome. The purpose was to evaluate the relationship between pain functional activities (WOMAC) and depression and overall health in individuals with ACL injuries. Methods: 50 Patients diagnosed with ACL injury, aged 15-45, were screened who fulfilled the inclusion criteria and were enrolled in the study after giving consent to the Department of Orthopaedics. The patients were asked questions related to their activities of daily life and mental health, including depression. Results: The study found a statistically significant moderate positive correlation between WOMAC scores and the Pain subdomain of the SF-36 (R=0.30, p=0.034). All other correlations, including WOMAC with PHQ-9 and other SF-36 dimensions, were weak and not statistically significant. Conclusions: The study indicates substantial differences in emotional (p=0.03) and general health (p=0.00) as critical emphasis areas, whereas other indicators had a minor effect on quality of life.